Biological Controls for Lebbeck Mealybug - Diepenbrock, Lauren Marie (EDIS, 2021)
Lebbeck mealybug (Nipaecoccus viridis) was first identified in Florida citrus in 2019 in Highlands County. It has now been documented in commercial citrus groves in 11 counties and in dooryard citrus plantings in two counties. There is no quick fix to getting control over lebbeck mealybug. But researchers are making progress each week to better understand this pest, its predators and what combination of management actions are needed to support Florida citrus production.